2010
DOI: 10.1002/chem.201002219
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole‐Bridged Porphyrin Nanorings

Abstract: Bridging the gap: A series of meso‐to‐meso pyrrole‐bridged cyclic porphyrins were prepared by a one‐pot Suzuki–Miyaura coupling reaction (see figure). The 1H NMR spectra of these compounds revealed their highly symmetric structures in solution, and the solid‐state structures of nickel and zinc derivatives were determined by X‐ray crystal analysis. The UV/Vis absorption spectra of the cyclic arrays indicate the strong excitonic interactions among porphyrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Despite these promises, pyrrole‐bridged porphyrin nanorings are rare. To the best of our knowledge, meso‐to‐meso pyrrole‐bridged porphyrin nanorings were synthesized as a single example by Suzuki–Miyaura crossing coupling of 5,10‐dibromoporphyrin and 2,5‐diborylpyrrole . As an extension of this work, we report the synthesis of β‐to‐β 2,5‐pyrrolylene‐bridged cyclic porphyrin dimer and trimer (Figure ).…”
Section: Figurementioning
confidence: 81%
See 1 more Smart Citation
“…Despite these promises, pyrrole‐bridged porphyrin nanorings are rare. To the best of our knowledge, meso‐to‐meso pyrrole‐bridged porphyrin nanorings were synthesized as a single example by Suzuki–Miyaura crossing coupling of 5,10‐dibromoporphyrin and 2,5‐diborylpyrrole . As an extension of this work, we report the synthesis of β‐to‐β 2,5‐pyrrolylene‐bridged cyclic porphyrin dimer and trimer (Figure ).…”
Section: Figurementioning
confidence: 81%
“…3,7‐Dibromo‐10,15,20‐triaryl Ni II porphyrin 1 Ni was prepared by bromination of 3,7‐diboryl‐10,15,20‐triaryl Ni II porphyrin with CuBr 2 in THF . Initially, Suzuki–Miyaura cross‐coupling of 1 Ni and 2,5‐diborylpyrrole was conducted under the same conditions used for meso‐to‐meso pyrrole‐bridged porphyrin arrays (Pd 2 (dba) 3 , PPh 3 , CsF, Cs 2 CO 3 , DMF, toluene, reflux, 24 h) . Mass analysis of the reaction mixture indicated formation of only linear oligomers and other unknown byproducts.…”
Section: Figurementioning
confidence: 99%
“…through synthesizing decaphyrins and octaphyrins with a bridging 1,4‐phenylene group . Additionally, the syntheses of multi‐annulated aromatic annulenes have been illustrated through the preparation of meso ‐to‐ meso 2,5‐pyrrolylene‐bridged cyclic porphyrin arrays . A recent study on expanded bi‐cyclic dithienothiophene‐bridged [34]octaphyrins confirmed the presence of dual conjugation pathways .…”
Section: Methodsmentioning
confidence: 99%
“…The Anderson group has developed a spectacular strategy with small templates to assist in the production of meso – meso big loops from porphyrin strands 2630. Recently, we found that the palladium‐catalyzed Suzuki–Miyaura cross‐coupling reaction was also very powerful in synthesizing covalently linked multiporphyrin arrays 15. 18 Azobenzene is also a well‐known and widely used chromophore, owing to its cis – trans photoisomerization.…”
Section: Introductionmentioning
confidence: 99%
“…[3] These cyclic and elegant porphyrin arrays also have potentialu ses in single-molecule photochemistry, [4] nonlinear optical (NLO) materials, [5] host-guest chemistry, [6,7] and other applications. [8][9][10][11][12][13][14] The meso-to-meso, [15][16][17] b-to-b [18][19][20][21] and mesoto-b [22] linked porphyrin wheelsc ould be constructedi nd ifferent ways. The Osuka group hasd eveloped silver(I)-promoted meso-meso coupling reactions of 5,15-diaryl-substituted zinc(II)-porphyrin and prepared two impressive hexagonal porphyrin wheels composed of 12 and 24 porphyrin units, respectively.…”
Section: Introductionmentioning
confidence: 99%